Women in chemistry: Q&A with Professor Aurora J. Cruz-Cabeza (Communications Chemistry)
Dr Aurora J. Cruz-Cabeza is a Professor of Materials Chemistry at Durham University, in the field of molecular crystals and crystallisation.